2022
DOI: 10.3390/ijerph19127030
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy: It Is Now Time to Put Knowledge into Practice

Abstract: The term ‘mental health literacy’ was first introduced in 1997, and it was defined as ‘knowledge and beliefs about mental disorders which aid their recognition, management or prevention’ [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Similarly, a previous study also reported the full mediating role of psychological capital between stress and coping styles in nurses working in the intensive care unit [ 49 ]. The finding of this study indicates that nurse managers and policymakers can support newly recruited nurses through these two routes [ 50 , 51 ]. First, a variety of education modalities to increase mental health literacy can be offered continuously after recruiting nurses in the hospital, especially the promotion of positive mental health maintenance and help-seeking efficacy and attitude, and the reduction of stigma attitude towards mental health disorders, which can be considered essential insights to improve coping styles.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous study also reported the full mediating role of psychological capital between stress and coping styles in nurses working in the intensive care unit [ 49 ]. The finding of this study indicates that nurse managers and policymakers can support newly recruited nurses through these two routes [ 50 , 51 ]. First, a variety of education modalities to increase mental health literacy can be offered continuously after recruiting nurses in the hospital, especially the promotion of positive mental health maintenance and help-seeking efficacy and attitude, and the reduction of stigma attitude towards mental health disorders, which can be considered essential insights to improve coping styles.…”
Section: Discussionmentioning
confidence: 99%
“…Istilah literasi kesehatan mental didefinisikan sebagai pengetahuan dan keyakinan tentang gangguan mental yang membantu mengenali gejala, dan melakukan pengelolaan dan pencegehahan gangguan mental. Hal ini mengacu pada sikap individu terhadap pengetahuan tentang gejala, penyebab, dan pengobatan, yang semuanya penting dalam memfasilitasi sikap pengakuan dan pencarian pengobatan untuk masalah gangguan mental (Vale-Dias et al, 2014;Sampaio, Gonçalves, & Sequeira, 2022;Trompeter et al, 2022).…”
Section: Pendahuluanunclassified
“…Some years later, Jorm reinforced the construction of the concept of MHL not only as a source of knowledge of mental disorders, but also as a person’s ability to put the acquired knowledge into actions for the benefit of their own health and that of the people around them [ 7 ]. Furthermore, mental health literacy should be seen as a construct that promotes positive mental health [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research carried out in these two domains has focused on adolescents and young adults [ 8 ], due to the significant prevalence of mental health disorders in this population and the early age of onset of several mental health disorders. However, there are other vulnerable populations that should be studied, such as older people and professionals in the social sector, health, or even education.…”
Section: Introductionmentioning
confidence: 99%